2016
DOI: 10.1007/s13205-016-0543-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of methods for metagenomic DNA isolation from soils of different crop growing fields

Abstract: The isolation of good quality metagenomic DNA from diverse soil, in appreciable amount, is a prerequisite for metagenomics. The availability of commercial kits for isolation of genomic DNAs from soil has drastically expedited the application of metagenomics approach for identifying novel sources of industrially important enzymes. The quantitative and qualitative assessment of metagenomic DNA isolated using either the manual method or the kit-based method should be performed prior to its use in downstream appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…2B; for proteins and phenol contamination; Maniatis et al 1982) and A260:230 ratios ( Fig. S2; for carbohydrates and phenols; Maniatis et al 1982;Tanveer, Yadav, and Yadav 2016). We posited that A260:280 is a more robust predictor of virome success, since previous work showed that A260:230 of DNA extracts had limited correlation to amplification success (Costa et al 2010;Ramos-Gómez et al 2014), although both are highly variable for low DNA concentrations typical for soil viral extracts.…”
Section: Experiments 1: Different Dna Extraction Methods Display Variamentioning
confidence: 73%
“…2B; for proteins and phenol contamination; Maniatis et al 1982) and A260:230 ratios ( Fig. S2; for carbohydrates and phenols; Maniatis et al 1982;Tanveer, Yadav, and Yadav 2016). We posited that A260:280 is a more robust predictor of virome success, since previous work showed that A260:230 of DNA extracts had limited correlation to amplification success (Costa et al 2010;Ramos-Gómez et al 2014), although both are highly variable for low DNA concentrations typical for soil viral extracts.…”
Section: Experiments 1: Different Dna Extraction Methods Display Variamentioning
confidence: 73%
“…Some researchers use different methods, depending on the type of research sample used [10]. Tanveer et al [27] have carried out DNA extraction of the metagenome using commercial kits and standard protocols. Metagenomic DNA extraction using commercial kits is the easiest method because it only uses chemicals that have been provided by the manufacturer.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…However, some studies that use standard protocols show better results when compared to kits. Tanveer et al [27] tried to compare the extraction of metagenomic DNA from the soil using the HiPurA soil DNA isolation kit (Himedia) and standard protocol. The results revealed that the standard protocol produced the highest concentration of DNA.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…As the physico-chemical properties of soil and sediment samples vary worldwide, it is difficult to develop a single, ideal total community DNA extraction protocol (Felczykowska et al 2015). A number of chemical, mechanical, and enzymatic methods and commercial kits have been developed to encounter this problem (Tsai and Olson 1991;Canto-Canche et al 2013;Tian et al 2013;Gutierrez-Lucas et al 2014;Devi et al 2015;Tanveer et al 2016). Moreover, several cell lysis methods and purification steps have been recommended for the efficient recovery of high quality metagenomic DNA.…”
Section: Introductionmentioning
confidence: 99%